The Influence Of Service Quality On Customer Satisfaction At J&T Express Pondok Suguh Of Mokomuko Regency - Julianti Br. Hutagaol; Siti Hanila; Yudi Irawan Abi (Penerbit Jurnal Indonesia, 2023)
Competition in goods delivery service companies is currently developing very rapidly. For this reason, every company owner must be able to create quality service that can increase consumer satisfaction. This research aims to determine the effect of service quality on consumer satisfaction at J&T Express Pondok Suguh, Mukomuko Regency. The sample in this study was 80 consumers who came to send packages and received packages at J&T Express Pondok Suguh, Mukomuko Regency. The sampling technique is accidental sampling technique. Data were collected using a questionnaire and the analysis methods used were simple linear regression, determination tests and hypothesis testing. The results of simple linear regression analysis show Y = 22.392 + 0.307X. This illustrates a significant regression direction, meaning that there is a significant influence between Service Quality (X) on Consumer Satisfaction (Y). This means that if the service quality variable increases, it will increase consumer satisfaction. The results of the t test at the level of α= 0.05 explain that the service quality variable has a significant influence on the consumer satisfaction variable at J&T Express Pondok Suguh, Mukomuko Regency. The value of the coefficient of determination is 0.222. This means that Service Quality (X) influences Consumer Satisfaction (Y) by 22.2% while the remaining 78.8% is influenced by other variables not examined in this research.